The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12223161
|View full text |Cite
|
Sign up to set email alerts
|

Handling, Reproducing and Cryopreserving Five European Sea Urchins (Echinodermata, Klein, 1778) for Biodiversity Conservation Purposes

Abstract: In this work, five local sea urchin species found in European waters were studied. Four were regular species: Sphaerechinus granularis, Psammechinus miliaris, Echinus esculentus (Linnaeus, 1758) and the edible sea urchin Paracentrotus lividus; and one was an irregular species, Echinocardium cordatum. These five species of sea urchins have been studied regarding their fertility, toxicity of cryoprotecting agents, cryopreservation of different cell types and chilling injury. The baseline fertility is similar in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…3 D–F, 4 D–F, 5 D–F, 6 D–F). These results are consistent with the LOEC (Lowest Observed Effect Concentration) values calculated by Paredes and Bellas 17 and Paredes et al 40 for DMSO, EG and PG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3 D–F, 4 D–F, 5 D–F, 6 D–F). These results are consistent with the LOEC (Lowest Observed Effect Concentration) values calculated by Paredes and Bellas 17 and Paredes et al 40 for DMSO, EG and PG.…”
Section: Discussionsupporting
confidence: 92%
“…Results have shown that exposing the eggs to low concentrations (0.5 M) of DMSO, EG and PG did not cause damage to the cells (Figs. 3 , 4 , 5 , 6 A–C) which is in agreement with prior data of CPA toxicity 17 , 40 . In the case of eggs, the NOEC (No Observed Effect Concentration) values calculated support the results obtained in this study, since after exposing those cells to low concentrations of CPA, the ultrastructure was similar to controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The history of cryopreservation of sea urchin sperm began in 1973 (9), and at present, sperm of about 15 species have been cryopreserved as recently reviewed (11,26-28,31). Cryopreservation of sperm of all animals involves dilution of concentrated semen into an extender solution and then mixing this cell suspension with a cryoprotectant such as dimethyl sulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, protocols need to be established, shared and standardized within the scientific community to successfully obtain gametes from different mollusks, as well as sea urchins, which also present with external fertilization. Sea urchins are model organisms and, therefore, some species of sea urchins, such as Strongylocentrotus purpuratus or Paracentrotus lividus, are quite well studied and have many protocols in place; however, this is not the case for other sea urchins [6], as it has been shown in many cases that protocols would have to be adapted to particular species. Important knowledge about reproduction is not often well-known or standardized, such as contact time, the egg:sperm ratio, optimum parameters for embryo incubation and expected outcome after larval rearing, but is key information for marine invertebrates [2,6].…”
mentioning
confidence: 99%